2020
DOI: 10.1007/s00429-020-02047-0
|View full text |Cite
|
Sign up to set email alerts
|

Principles of temporal association cortex organisation as revealed by connectivity gradients

Abstract: To establish the link between structure and function of any large area of the neocortex, it is helpful to identify its principles of organisation. One way to establish such principles is to investigate how differences in whole-brain connectivity are structured across the area. Here, we use Laplacian eigenmaps on diffusion MRI tractography data to investigate the organisational principles of the human temporal association cortex. We identify three overlapping gradients of connectivity that are, for the most par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 70 publications
1
20
0
Order By: Relevance
“…In particular, recent work has shown that there are white matter tracts that terminate along the superior temporal gyrus-inferior temporal gyrus axis (Bajada, Jackson, et al, 2017;Blazquez Freches et al, 2020). These in part overlap with terminations of the arcuate fasciculus along the posterior-anterior axis Blazquez Freches et al, 2020). It is therefore possible that the resting-state fMRI derived connectopic maps that we obtained reflect the individual-level organization of white matter tract terminations in the ATL.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In particular, recent work has shown that there are white matter tracts that terminate along the superior temporal gyrus-inferior temporal gyrus axis (Bajada, Jackson, et al, 2017;Blazquez Freches et al, 2020). These in part overlap with terminations of the arcuate fasciculus along the posterior-anterior axis Blazquez Freches et al, 2020). It is therefore possible that the resting-state fMRI derived connectopic maps that we obtained reflect the individual-level organization of white matter tract terminations in the ATL.…”
Section: Discussionmentioning
confidence: 71%
“…Given the structural connectivity of the ATL with modality-specific and language areas, it is likely that the gradients are in part driven by terminations of long-range white matter tracts. In particular, recent work has shown that there are white matter tracts that terminate along the superior temporal gyrus-inferior temporal gyrus axis (Bajada, Jackson, et al, 2017;Blazquez Freches et al, 2020). These in part overlap with terminations of the arcuate fasciculus along the posterior-anterior axis Blazquez Freches et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We enhanced this vertex-wise approach with manifold learning techniques that allow for the low-dimensional representation of spatial variations in temporal lobe structural connectivity. Already established by previous neuroimaging studies (Bajada et al, 2019; Blazquez Freches et al, 2020; Haak et al, 2018; Huntenburg et al, 2017; Margulies et al, 2016; Paquola et al, 2019), these techniques are able to model both gradual and overlapping modes of connectivity without reliance on a priori boundaries (Haak & Beckmann, 2020). Recapitulating prior work, we found that the temporal lobe is best described by three gradients (Bajada et al, 2019; Blazquez Freches et al, 2020), spanning medio-lateral (G1), anterior-posterior (G2) and anterolateral-posteromedial (G3) axes.…”
Section: Discussionmentioning
confidence: 99%
“…Capitalizing on resting-state functional MRI acquisitions, gradient mapping techniques have previously identified principal axes of neural organization in healthy adults and in non-human primates (Buckner & Margulies, 2019; Guell et al, 2018; Haak et al, 2018; Margulies et al, 2016; Vos de Wael et al, 2018; Xu et al, 2020), and these techniques are increasingly used to study lifespan processes related to aging (Lowe et al, 2019; Bethlehem et al, 2020) and typical as well as atypical childhood development (Ball, Seidlitz, Beare, et al, 2020; Ball, Seidlitz, O’Muircheartaigh, et al, 2020; Hong, Vos de Wael, et al, 2019; Larivière et al, 2019; Park, Hong, et al, 2020). In the temporal lobe, these techniques have previously been applied to structural connectivity information, with the goal of subsequent parcellation (Bajada et al, 2017), to describe the ventral and anterior temporal lobe as a structural connectivity convergence zone (Bajada et al, 2019), and to relate structural connectivity gradients to meta-analytic task activations (Blazquez Freches et al, 2020; Yarkoni et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The frontal regions that should be considered for inclusion in ExtPFIT are adjacent to the PFIT but more posterior (somatosensory gyrus), medial (medial superior frontal gyrus), and inferior (orbital), suggesting the contribution of top-down regulatory systems for cognitive performance (Hampshire et al 2010, Swick, Ashley and Turken 2008, Rolls and Grabenhorst 2008, Wojtasik et al 2020. The parietal candidates for ExtPFIT are the supramarginal and angular gyri, regions long implicated in complex cognition (Geschwind 1970, Tremblay andDick 2016), as is the temporal pole, a region implicated in multimodal sensory integration (Olson, Plotzker and Ezzyat, 2007) and social cognition (Pehrs et al 2017), underscoring the role of temporal lobe connectivity in complex cognition (Blazquez Freches et al 2020). The occipital region that could be included in…”
Section: Data-driven Analysesmentioning
confidence: 99%